Modern Strategies to Develop Reading Skills/الاستراتيجيات الحديثة لتطوير مهارة القراءة - Zamroni, Ahmad (JURNAL IJ-ATL, 2017)
The reading skill is one of the language skills that must be developed, cause reading is knowledge key in human life and it is most needed for human learning and education, as confirmed by the Koran, In it’s verse: read the name of your Lord who created. Many modern strategies such as: the SQ3R strategy, PQ4R strategy, strategy of 3P.A.S for quick reading, strategy of K.W.L.H To observe the cognitive development. These modern strategy can develope reading skill with its steps which are different from old reading steps. These modern strategies can be applied in school level to university level to enable students on reading comprehension.إن مهارة القراءة إحدى المهارات اللغوية التي لابد من تطويرها، وذالك لأن القراءة  لاتزال مفتاح المعارف في الحياة البشرية، وأن الحاجة إليها ماسة لأنها أساس تعلم الإنسان وتعليمهم كما أكّدها القرآن الكريم بقوله الله تعالى : ﴿اقرأ باسم ربك الذي خلق …﴾. فاستراتيجياتها الحديثة كثيرة وهي:  استراتيجية الخطوات الخمس (SQ3R)، إستراتيجية PQ4R ، إستراتيجية (3P.A.S) للقراءة السريـعة، إستراتيجية (K.W.L.H) لمراقبة النّمو المعرفي. وهذه الإستراتيجية الحديثة تستطيع أن تطوّر مهارة القراءة بخطواتها التي تختلف بخطوات القراءة القديمة. وهذه الإستراتيجية الحديثة يمكن تطبيقها للمرحلة المدرسية حتى المرحلة الجامعية لتمكين الطلاب على فهم المقروء.